2016
DOI: 10.4038/jbs.v3i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Income Diversification of Estate Sector in Sri Lanka

Abstract: This study aims to identifying determinants of income diversification at household level in Sri Lankan estate sector. Analysis builds on data of Household Income and Expenditure Survey 2009/2010 conducted by Department of Census and Statistics of Sri Lanka. The data set covered 1736 households in Sri Lankan estate sector. Herfindhal Index was applied to calculate income diversification at household level and Censored Tobit model was used to identify the determinants of income diversification. The econometric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…This ethnographic substudy was conducted using a four‐phase, mixed methods formative research design across six sites located in the rural, urban and estate (i.e., areas primarily growing marketable crops such as tea for export), sectors of Sri Lanka (Bernard, 2011; Creswell, 2008; Dharmadasa & Polkotuwa, 2016). Data were collected between September 2020 and September 2021 by a team of locally‐hired data collectors who had postgraduate educations and language proficiencies needed for fieldwork among both Tamil and Sinhalese‐speaking community members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ethnographic substudy was conducted using a four‐phase, mixed methods formative research design across six sites located in the rural, urban and estate (i.e., areas primarily growing marketable crops such as tea for export), sectors of Sri Lanka (Bernard, 2011; Creswell, 2008; Dharmadasa & Polkotuwa, 2016). Data were collected between September 2020 and September 2021 by a team of locally‐hired data collectors who had postgraduate educations and language proficiencies needed for fieldwork among both Tamil and Sinhalese‐speaking community members.…”
Section: Methodsmentioning
confidence: 99%
“…This ethnographic substudy was conducted using a four-phase, mixed methods formative research design across six sites located in the rural, urban and estate (i.e., areas primarily growing marketable crops such as tea for export), sectors of Sri Lanka (Bernard, 2011;Creswell, 2008;Dharmadasa & Polkotuwa, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies mainly focused on identifying the patterns and the determinants of income diversification of households in Sri Lanka, especially in agriculture-related households. Study by Dharmadasa and Polkotuwa (2016) found that gender and age of the household head, household size, ownership of agricultural land, number of workers above 15 y old and availability of migrants in a household have significantly contributed to the likelihood of having diversified income in the estate sector. Another study conducted by Hewavitharana and Dharmadasa (2016) focused on estate sector households in Badulla district.…”
Section: Income Diversification In Sri Lankamentioning
confidence: 99%
“…There are very limited studies on income diversification in Sri Lanka (Dharmadasa and Polkotuwa, 2016;Jayamanna et al, 2015;Hewavitharana and Dharmadasa, 2016). Previous studies mainly focused on identifying the patterns and the determinants of income diversification in Sri Lankan households.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are large inequalities in access to and the utilization of services (mainly health, and education) between the estate sector and the rest of the country (Jayawardena, 2014). Less market access, poor infrastructure and low levels of education are few major barriers that directly influence the adaptation of migration strategy of the estate workers' from the estates to urban areas or to foreign countries to meet their basic needs such as food, shelter, healthcare, and fulfillment of children's needs (Dharmadasa and Polkotuwa, 2016). Household and individual wellbeing is also indirectly affected by migration and remittances sent by migrants.…”
Section: Introductionmentioning
confidence: 99%